Effect of Nanodiamonds on Friction Reduction Performance in Presence of Organic and Inorganic Friction Modifiers - A. K. Piya; L. Yang; N. Emami; A. Morina (Lubricants)
The strive to reduce harmful emissions from transport has resulted in an increased emphasis on minimising friction in lubricated contacting components to improve the energy efficiency of automotive engines. In this sense, it is of particular interest to investigate whether a synergistic tribological performance could be achieved by combining two or more friction modifier additives with nanoparticles. This study conducts a comprehensive investigation into the tribological characteristics of lubricant formulations enriched with nanodiamonds (NDs), combined with organic (Glycerol Monooleate, GMO) and inorganic (molybdenum dithiocarbamate, MoDTC) friction modifiers and a low-concentration anti-wear additive (Zinc dialkyl dithio-phosphate, ZDDP). The interaction between NDs and MoDTC has been evaluated using reciprocal sliding tests at two different temperatures. The outcomes of the tribological experiments revealed that the interaction of NDs and MoDTC can enhance the friction and wear performance of steel pairs. However, this enhanced performance is shown to highly depend on other additives present in the lubricant mixture. Analysis of wear scars using High-Resolution Transmission Electron Microscopy (HRTEM), Atomic Force Microscopy (AFM) and Raman spectroscopy reveals that when NDs are fully entrapped into the formed tribofilm that contains the MoDTC-derived MoS2 layer, the lowest friction coefficient can be achieved.